Social issues in public education - Bartky, John A. (Boston, Massachusetts : Houghton Mifflin Company, 1963)
Public education is heavy with perplexing questions concerning its basic ideals and functions. How is education now organized, and how should it be organized? How does it now relate to other institutions, and how might these relationships be improved? What role should education play in the resolution of social issues? In an evolving society the answers to these and other crucial questions defy ultimate and absolute definition. Each new generation must find its own solutions and answers; and the purpose of this book is to assist future teachers and citizens in the endeavor.
Part One. The Educational Institution -- Part Two. School Interaction with social institution -- Part Three. The School and the social problems.
Includes bibliographical references and index.
Keywords: EDUCATIONAL SOCIOLOGY